2013
DOI: 10.1097/dbp.0b013e31829c44a2
|View full text |Cite
|
Sign up to set email alerts
|

Pornography Consumption, Sexual Experiences, Lifestyles, and Self-rated Health Among Male Adolescents in Sweden

Abstract: The boys, defined as frequent users of pornography, were more sexually experienced, spent more time at the computer, and reported an unhealthier lifestyle compared with average and nonfrequent users. No differences regarding self-rated health were detected even though obesity was twice as common among frequent users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 31 publications
2
41
0
2
Order By: Relevance
“…In a cross-sectional survey of 4,600 Dutch 15-to 25-year-olds, Hald, Kuyper, Adam, and de Wit (2013) reported that more than 88% of male and 44% of female participants had used SEM in the past 12 months. Comparable findings were reported in a population-based Swedish study, in which 95% of the surveyed male 16-year-olds used SEM (Mattebo, Tyden, Haggstrom-Nordin, & Nilsson, 2013). In an earlier study, the 2010 retrospective assessment of early SEM use in a national probability based sample of Croatian emerging adults, a substantial minority (40% of female and 39% of male participants) reported exposure to SEM before the age of 15 (Sinković, Štulhofer, & Božić, 2013).…”
Section: Introductionmentioning
confidence: 49%
“…In a cross-sectional survey of 4,600 Dutch 15-to 25-year-olds, Hald, Kuyper, Adam, and de Wit (2013) reported that more than 88% of male and 44% of female participants had used SEM in the past 12 months. Comparable findings were reported in a population-based Swedish study, in which 95% of the surveyed male 16-year-olds used SEM (Mattebo, Tyden, Haggstrom-Nordin, & Nilsson, 2013). In an earlier study, the 2010 retrospective assessment of early SEM use in a national probability based sample of Croatian emerging adults, a substantial minority (40% of female and 39% of male participants) reported exposure to SEM before the age of 15 (Sinković, Štulhofer, & Božić, 2013).…”
Section: Introductionmentioning
confidence: 49%
“…In particular, some authors have pointed out that the consumption of pornography can affect lifestyle choices, especially sexual habits (14). Many studies considered pornography consumption among adolescents a significant influence on their sexual attitudes and behaviors (15,16). The main reasons that motivate young people to consume pornography are curiosity, stimulus to masturbation, new knowledge and dating, exposure and exploration of (virtual) sex, and protected sexuality.…”
Section: Discussionmentioning
confidence: 99%
“…Increased pornography viewing has been associated with younger sexual debut, higher numbers of partners and casual sex partners 9 15 16. Certain sexual risk behaviours that are not widely practised among heterosexuals occur commonly in pornography; a content analysis found that 28% of scenes include sex between three or more people 12.…”
Section: Sexual Risk Behaviourmentioning
confidence: 99%